2018
DOI: 10.17736/ijope.2018.ak28
|View full text |Cite
|
Sign up to set email alerts
|

On the Coupling of Incompressible SPH with a Finite Element Potential Flow Solver for Nonlinear Free-Surface Flows

Abstract: This paper presents a two-dimensional, one-way coupling methodology between the quasi-arbitrary Lagrange-Euler finite element method (QALE-FEM) nonlinear potential flow solver and the incompressible smoothed particle hydrodynamics (ISPH) Navier-Stokes equations solver. Nonlinear potential flow solvers such as the QALE-FEM are highly efficient solvers for propagating waves in large domains; however, when extreme nonlinearity takes place, such as fragmentation, breaking waves, and violent interaction with marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…the wave propagation away from the structures, the effective FNPT models are employed. Typical examples include the coupling of the FNPT with commercial software (Yan and Ma, 2010b;Hildebrandt and Sriram, 2014), with the single-phase MLPG-R (Sriram et al, 2014; or SPH (Fourtakas et al, 2018), and with OpenFOAM (Li et al, 2018), which were developed based on the domaindecomposition strategy. It is worth noting that hybrid models using the velocity-decomposition strategy have also been developed to tackle the challenges in the WSIs (Edmund et al, 2013;Ferrant et al, 2003Ferrant et al, , 2008Luquet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…the wave propagation away from the structures, the effective FNPT models are employed. Typical examples include the coupling of the FNPT with commercial software (Yan and Ma, 2010b;Hildebrandt and Sriram, 2014), with the single-phase MLPG-R (Sriram et al, 2014; or SPH (Fourtakas et al, 2018), and with OpenFOAM (Li et al, 2018), which were developed based on the domaindecomposition strategy. It is worth noting that hybrid models using the velocity-decomposition strategy have also been developed to tackle the challenges in the WSIs (Edmund et al, 2013;Ferrant et al, 2003Ferrant et al, , 2008Luquet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…the velocity-decomposition (Edmond et al, 2013), spacesplitting /domain-decomposition (e.g. Colicchio et al, 2006;Yan and Ma, 2010a;Hildebrandt et al, 2013;Sriram et al 2014;Fourtakas et al 2017;Li et al 2018;Zhang et al 2020) and time-splitting approaches (e.g. Wang et al, 2018) have been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrant et al, 2003;Luquet et al, 2007, Ferrant et al, 2008Edmund et al, 2013) and the domain-decomposition (e.g. Yan and Ma 2010;Hildebrandt et al, 2013;Sriram et al, 2014;Fourtakas et al, 2017;Higuera et al, 2018; have been developed. Systematic reviews on the development of the hybrid models can be found in Sriram et al, (2014) and .…”
Section: Introductionmentioning
confidence: 99%